Odpowiedź :
Odpowiedź:
a) 3x-8=-7
3x=1
x=3
b)4x-2=-2
4x=0
x=0
c) 15x+19=10
15x=-9
x=- 15/9
a) 3x-8=2x+4
3x-2x=4+8
x=12
b)5x-3=4x+6
x=9
c) 7x-9=6x-8
x=1
Poz. A
a) 3x-8=-7
3x=8-7
3x=1
x=1/3
b) 4x-2=-2
4x=-2+2
4x=0
0=0
c) 15x+19=10
15x=10-19
15x=-9
x=-0,6
d) 2x+9=1
2x=1-9
2x=-8
x=-4
e) 7x-9=5
7x=5+9
7x=14
x=2
f) 8x-5=-7
8x=-7+5
8x=-2
x=0,25
g) 9x-40=14
9x=14+40
9x=54
x=6
h) 20x+7=31
20x=31-7
20x=24
x=1,2
i) 6x-25=-25
6x=25-25
6x=0
0=0
Poz. B
a) 3x-8=2x+4
3x-2x=4+8
x=12
b) 5x-3=4x+6
5x-4x=6+3
x=9
c) 7x-9=6x-8
7x-6x=9-8
x=1
d) 7x-5=6x+8
7x-6x=8+5
x=13
e) 5x-8=4x+9
5x-4x=9+8
x=17
f) 9x-4=8x+5
9x-8x=5+4
x=9
g) 12x+4=11x+15
12x-11x=15-4
x=11
h) 3x-1=2x+1
3x-2x=1+1
x=2
i) 2x+7=x-1
2x-x=-1-7
x=-8